2011
DOI: 10.1093/jac/dkr159
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic safety of antibiotics used in primary care

Abstract: Antibiotics used by general practitioners frequently appear in adverse-event reports of drug-induced hepatotoxicity. Most cases are idiosyncratic (the adverse reaction cannot be predicted from the drug's pharmacological profile or from pre-clinical toxicology tests) and occur via an immunological reaction or in response to the presence of hepatotoxic metabolites. With the exception of trovafloxacin and telithromycin (now severely restricted), hepatotoxicity crude incidence remains globally low but variable. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
138
1
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(159 citation statements)
references
References 178 publications
5
138
1
10
Order By: Relevance
“…The true incidence of DILI associated with antimycotics in the post-marketing phase challenges precise estimation, especially as compared to other antimicrobials [27] . Previous studies, mostly based on data derived from clinical trials, reported a 2%-23% range, depending on the drug of interest and especially the severity of the disease [28] .…”
Section: Antimycotics and Dili: Clinical And Regulatory Aspectsmentioning
confidence: 99%
“…The true incidence of DILI associated with antimycotics in the post-marketing phase challenges precise estimation, especially as compared to other antimicrobials [27] . Previous studies, mostly based on data derived from clinical trials, reported a 2%-23% range, depending on the drug of interest and especially the severity of the disease [28] .…”
Section: Antimycotics and Dili: Clinical And Regulatory Aspectsmentioning
confidence: 99%
“…Antibiyotiklerin neden olduğu hepatotoksisite tanısı, serum alanin aminotransferaz (ALT) ve bilirubin düzey-lerinin 2 katından daha fazla düzeye çıkması ile belirlenebilmektedir. İnsanlarda antibiyotik kaynaklı hepatotoksisitenin görülme oranı yaklaşık <5/100.000 (Andrade and Tulkens 2011), makrolid antibiyotiklerin neden olduğu hepatotoksisite oranı ise yaklaşık 3.6/100.000 civarındadır (Leitner 2010). Canlıda gözlenen hepatotoksisitenin tanımlanabilme-si için kandan alkalen fosfataz (ALP), bilirubin, ALT, aspartat aminotransferaz (AST), gamma glutamiltransferaz (GGT), total protein ve albümin düzeyleri ölçümü yapılmaktadır.…”
Section: Introductionunclassified
“…Austin et al 17 recorded a significant decreasein the albumin in the serum of mice after treatment with penicillin (10000 IU and 250000 IU/kg) for 21 days. The side effects which associate with the therapy by penicillin is mainly due the generation of an excessive amount of reactive oxygen species (ROS), resulting in the detrimental effects of the cellular antioxidant defense system, as well as, enhancement of the lipid peroxidation (LPO) process 18,19 . Reactive oxygen species (ROS) are an inevitable byproduct of cellular respiration causing oxidation of lipids, nucleic acids, and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) are an inevitable byproduct of cellular respiration causing oxidation of lipids, nucleic acids, and proteins. The (ROS) damage is an underlying cause of disease, including cancer, inflammatory, and neurodegenerative diseases [20][21][22] , Liver disease 19 . Antioxidants protect key cell components from damage by neutralizing the free radicals 23 .…”
Section: Introductionmentioning
confidence: 99%